Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Middle East Dancer Cory Zamora wearing golden bikini and dancing in front of seated Howard Watkins with black cape around his neck Crowd standing behind Howard looking on